Marine antioxidants : preparations, syntheses, and applications - Kim, Se-Kwon; Shin, Kyung-Hoon; Venkatesan, Jayachandran (Academic Press, an imprint of Elsevier, 2023)
"Marine Antioxidants: Preparations, Syntheses, and Applications provides the most updated and comprehensive knowledge on utilizing marine-derived substances for cosmeceutical, pharmaceutical and nutraceutical developments. The book delivers the isolation procedures and biological activity of marine-derived antioxidant substances as discussed by international experts on antioxidant material from actinobacteria, crustaceans, diatoms, fish, microalgae, microbes, and mangrove-associated marine organisms and seagrasses. In addition, the book details marine-derived bioactive antioxidants substances in the form of proteins, peptides, polysaccharides and lipids. Finally, the book provides the latest information on the mechanistic pathways of antioxidant substances with various diseases and nutritional perspectives."--Publisher.